2020
DOI: 10.1253/circj.cj-19-0823
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Preoperative Computed Tomography Assessment of the Membranous Septal Anatomy in Patients Undergoing Transcatheter Aortic Valve Replacement With a Balloon-Expandable Valve

Abstract: sistent on the association of CD with MS in patients with a balloon-expandable valve (BEV). 9,10 Therefore, we examined whether computed tomography (CT) assessment of the MS anatomy could provide useful information about the risk of CD, PPM implantation or CLBBB, following TAVR with BEV. Methods Study Population The study population comprised 132 consecutive patients with symptomatic severe AS who underwent TAVR at Kyoto Prefectural University of Medicine between February 2016 and July 2019; 26 patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…After excluding duplicates and noneligible studies, 18 studies 4,6,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] met our eligibility criteria (Supporting Information: Figure 1). All the studies were nonrandomized and observational, while four studies were multicentric and five studies included matched populations (Table 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…After excluding duplicates and noneligible studies, 18 studies 4,6,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] met our eligibility criteria (Supporting Information: Figure 1). All the studies were nonrandomized and observational, while four studies were multicentric and five studies included matched populations (Table 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Chen, et al reported an ∆MSID of 3.2 mm to be the optimal cutoff point for predicting a CD when using a self -expanding device [21]. For balloon expanding TAVR, mean ∆MSIDs of − 2.5 ± 2.4 mm [23], 0.5 ± 4 mm [24], and − 1.7 ± 1.5 mm [27] were reported in patients with PPMI or LBBB. Miki, et al reported that an ∆MSID cut-off value of -0.7 mm had an AuROC of 0.85, sensitivity of 0.78, and specificity of 0.82 (p < 0.001).…”
Section: Postprocedural Outcomementioning
confidence: 99%
“…Finally, we did not measure the membranous septum, which could be an interesting aspect, associated to the implantation height, to stratify the risk of conduction disorders after TAVI. 30 An ancillary analysis of STIM-TAVI (STIM-TAVI/MS) is currently running, in which we are analyzing membranous septum length and implantation height.…”
Section: Limitationsmentioning
confidence: 99%